2017
DOI: 10.3390/rs9010039
|View full text |Cite
|
Sign up to set email alerts
|

Woody Vegetation Die off and Regeneration in Response to Rainfall Variability in the West African Sahel

Abstract: Abstract:The greening in the Senegalese Sahel has been linked to an increase in net primary productivity, with significant long-term trends being closely related to the woody strata. This study investigates woody plant growth and mortality within greening areas in the pastoral areas of Senegal, and how these dynamics are linked to species diversity, climate, soil and human management. We analyse woody cover dynamics by means of multi-temporal and multi-scale Earth Observation, satellite based rainfall and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 39 publications
8
78
0
Order By: Relevance
“…The increase is more pronounced in protected areas ("forêts classées") than in reforestation areas such as the Great Green Wall. As previously observed by Hiernaux et al [85], Gardelle et al [48], Dardel et al [13] in Eastern Mali, Brandt et al [15] showed that in Senegal too, lower vegetation recovery occurred over shallow soils (here in ferrugineous plateaus of the Ferlo), where they observed "mass dying of trees on lateritic soils during droughts". Bamba et al [90] observed that the increasing trend in vegetation greenness is extending from the South to North.…”
Section: Evaluation Of Global Vegetation Evolution Through Remote Sensupporting
confidence: 60%
See 4 more Smart Citations
“…The increase is more pronounced in protected areas ("forêts classées") than in reforestation areas such as the Great Green Wall. As previously observed by Hiernaux et al [85], Gardelle et al [48], Dardel et al [13] in Eastern Mali, Brandt et al [15] showed that in Senegal too, lower vegetation recovery occurred over shallow soils (here in ferrugineous plateaus of the Ferlo), where they observed "mass dying of trees on lateritic soils during droughts". Bamba et al [90] observed that the increasing trend in vegetation greenness is extending from the South to North.…”
Section: Evaluation Of Global Vegetation Evolution Through Remote Sensupporting
confidence: 60%
“…This demonstrates the resilience of Sahelian ecosystems, although this trend is generally observed in places with low human pressure. Brandt et al [15] further identified the pastoral area of Senegal as the area with the largest increase in woody cover within the Sahel. The increase is more pronounced in protected areas ("forêts classées") than in reforestation areas such as the Great Green Wall.…”
Section: Evaluation Of Global Vegetation Evolution Through Remote Senmentioning
confidence: 99%
See 3 more Smart Citations